Coupled effect of relative humidity and temperature on the degradation of cement mortars partially exposed to sulfate attack. (20th August 2019) - Liu, Chuanbei; Gao, Jianming; Chen, Fei; Zhao, Yasong; Chen, Xuemei; He, Zhizhang
Highlights: The driving damage mechanism for partially immersed cement mortars was examined. Lowering the RH would accelerate physical sulfate attacks in drying parts. An intermediate temperature of 35 °C causes more serious degradation than 20 and 50 °C. Abstract: Concrete structures in salt lakes of western China and South China Sea deteriorate dramatically because of the aggressive salt, high temperature and low relative humidity (RH). In order to study the deterioration mechanism of cement-based materials in these severe environments, the damage progress of mortar specimens that partially exposed to sulfate solutions and under different ambient RH and temperatures was examined. The results indicate that the driving deterioration mechanism for cement mortars that partially exposed to Na2 SO4 solution is physical attacks in drying portions, while it is chemical attacks in immersed portions for cement mortars that partially exposed to MgSO4 solution. Besides, lowering the ambient RH (e.g., from 80% to 50% and 30%) would promote a narrow but supersaturated evaporation interface zone, which accelerates the salt crystallization and eventually surface scaling. While the relatively high ambient RH (80%) causes a broad diffusion zone where the chemical related expansion and cracking formed. Moreover, an intermediate temperature of 35 °C is proved to produce the most severely deterioration when compared to the temperature of 20 and 50 °C.